Zwartkoppies farm complex : exploiting a redundant cultural landscape for social, ecological and economical development - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2013)
Dissertation ML(Prof)--University of Pretoria, 2014.